Resiliensi Sosial Nelayan Kamal Muara dalam Menghadapi Dampak Reklamasi Teluk Jakarta - Triyanti Anugrahini (Jurnal Penelitian Kesejahteraan Sosial, 2018)
Reclamation along the Jakarta Bay has caused an impact on both the ecological and social system. This research is aimed to describe the impact of reclamation and that of resilience of fishermen in Kamal Muara village, Penjaringan, North Jakarta in coping with the impact of reclamation. Using qualitative approach, data are gathered through document studies, observations and in-depth interviews of 11 fishermen who have boat capacity of 5 GT or small scale boat capacity and who conduct fishing in shallow water along Jakarta Bay. The results showed that the impact of reclamation were the fishing area was getting narrower from time-to-time, access to the water and fishing area is getting more difficult and consequently the catches shrink and the emergence of the threat of extinction as a fisherman. Meanwhile, the resilience of small fishermen is getting worse and vulnerable when the reclamation activities are intensified during 2014-2015, when the development of Pulau C and D is on going.